Linking solar-induced chlorophyll fluorescence to biogenic volatile organic compound emissions in low Arctic tundra: A field spectroscopy approach - Federico Grillini; Simon Nyboe Laursen; Amy Smart; Peiyan Wang; Shunan Feng; Juliane Bendig; Andreas Westergaard-Nielsen (Remote Sensing of Environment, 2026)

Multi-source remote sensing of insect defoliation events in Abisko from point to regional scales - Shunan Feng; Simon Nyboe Laursen; Amy Smart; Katrine Stadsholt Sørensen; Monika Lund; Federico Grillini; Jolanta Rieksta; Yi Jiao; Riikka Rinnan; Andreas Westergaard-Nielsen (Agricultural and Forest Meteorology, 2026)

Net emission of atmospheric volatile organic compounds from ponds in a peatland forest - Yinghuan Qin; Kajsa Emilia Roslund; Amy Samantha Smart; Jesper Riis Christiansen; Riikka Rinnan (Limnology and Oceanography, 2025)
The role of small water bodies in global carbon emissions is increasingly acknowledged. In addition to the well‐investigated greenhouse gases, carbon dioxide (CO 2 ) and methane, volatile organic compounds (VOCs) may be emitted from freshwater ecosystems, especially from small water bodies, but the composition of emitted VOCs and emission magnitudes remain largely undescribed. Referring to empirical great contributors of freshwater greenhouse gases, we assessed seasonal VOC emissions from three carbon and nutrient‐rich ponds in a peatland forest in Denmark. These ponds were CO 2 emitters throughout the sampling period (19.5 ± 67.7 to 396.8 ± 120.0 mg m −2 h −1 ). The total net fluxes of > C5 VOCs measured in situ ranged from 7.8 ± 1.4 to 95.3 ± 4.5 μ g m −2 h −1 and over one hundred compounds were detected. The emissions consisted mainly of hydrocarbons, oxygenated VOCs, and terpenoids (isoprene, monoterpenoids, and sesquiterpenoids). We found the in situ VOC fluxes and compositions varied with season and were positively correlated with chamber temperature. These fluxes also differed between ponds and were related to the chemical properties of pond water. Additionally, we observed emissions of significant and various lighter VOCs (

Black Sea Bass Centropristis striata Year Class Strength and Spatial Extent from Two Long-Term Surveys off the Southeast U.S. Atlantic Coast - Julie L. Vecchio; Margaret W. Finch; Kevin R. Spanik; Amy Zimney; Tracey I. Smart (Fishes, 2025)
The Southeastern U.S. Atlantic coast (North Carolina to Florida, U.S.A.) has undergone considerable environmental change in recent decades, including increasing coastal water temperature and human development. The region is also home to a diverse suite of exploited reef fish species, including the southern stock of black sea bass (Centropristis striata). The objective of the current study was to compare trends in black sea bass year class strength and central location captured by trawls (age 0) and traps (age 2) as well as compare those trends to regional bottom temperature. We found no correlation between age 0 and age 2 abundance when comparing the same year class, suggesting that the numbers of trawl-caught juveniles cannot predict the number of adults available to the fishery. Larger year classes observed in traps were correlated with centers of abundance farther south in the region, while smaller year classes corresponded with more northerly centers of abundance. In both trawls and traps, strong year classes occurred following years with below-average regional water temperatures, and a series of recent, weak year classes correspond with recent higher-than-average water temperatures. It is unclear whether correlations between shifting centers of abundance, year class strength, and regional bottom temperature indicate a range contraction for the southern stock of black sea bass or movement into areas previously inhabited by the northern stock of the species.

An adaptable integrated modelling platform to support rapidly evolving agricultural and environmental policy - Paula A. Harrison; Kate Beauchamp; Joe Cooper; Ian Dickie; Alice Fitch; Richard Gooday; Michael Hollaway; Ian P. Holman; Merryn Hunt; Laurence Jones; Thomas Mondain-Monval; Daniel Sandars; et al. (Environmental Modelling & Software, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.